Tourism, transport, and land use: a dynamic impact assessment for Kaohsiung's Asia New Bay Area. Issue 4 (1st October 2020) - Man, Chun-Yin; Shyr, Oliver F.; Hsu, Yi-Ya; Shepherd, Simon; Lin, Han-Liang; Tu, Chien-Hung
ABSTRACT: This paper proposes a hybrid methodology for analysing the causal relations between public transportation development, tourism and land use by combining System Dynamics (SD) with Geographical Information Systems (GIS) and agent-based modelling (ABM). It is applied to illustrate the quantitative and spatial effect of the two phases Light Rail Transit (LRT) development in Asia New Bay Area, Kaohsiung, Taiwan. This paper also furthers the application of the ABM spatial information as interactive variables in the stocks-flow model. The simulation results support that development policies of LRT are significant to the future tourism in Asia New Bay Area, while the under debate second phase of LRT is estimated to raise the number of visitors in long term by alleviating the deteriorating road traffic congestion. This policy-oriented simulation can serve as a reference to the decision-makers towards the future management of LRT.